Role of the World Organisation for Animal Health in global wildlife disease surveillance - Thompson, Lesa; Cayol, Claire; Awada, Lina; Muset, Sophie; Shetty, Dharmaveer; Wang, Jingwen; Tizzani, Paolo (Frontiers in Veterinary Science, 2024)
This paper examines the role of the World Organisation for Animal Health (WOAH) in the global surveillance and management of pathogens. Since the creation of WOAH, one of its missions has been to ensure transparency of the global animal health situation. WOAH established a Working Group on Wildlife in 1994 to inform and advise WOAH Members, leadership, and technical teams on issues relating to wildlife health. In 2020 it conducted a consultation with its Members before developing a Wildlife Health Framework to improve global health and wildlife conservation.WOAH Members report diseases in wildlife, but detections are dependent on the surveillance systems in place. As an example of data collected in the most recent years (2019 -2023), 154 countries have reported 68,862,973 cases, through alert messages and weekly updates, for 84 diseases. One-hundred and fifty countries have reported 68,672,115 cases in domestic animals and 95 countries have reported 190,858 cases in wild animals. These figures illustrate the performance of the organisation in collecting data on wildlife, and provide an indication of the difference in completeness of data collected in domestic animals and wildlife. There are several challenges to wildlife disease surveillance and real figures remain unknown; they depend on the existence, quality and sensitivity of national surveillance. A WOAH-led One Health approach with crosssectoral collaboration is needed to improve surveillance sensitivity, address the challenges and help safeguard wildlife population health and biodiversity conservation.